Biological activities of the rice bran extract and physical characteristics of its entrapment in niosomes by supercritical carbon dioxide fluid - Manosroi A. (2014)
The objectives of this study were to compare the biological activities of the rice bran (Oryza sativa Linn.) extracts prepared by supercritical carbon dioxide fluid (scCO2) and ethanolic maceration, and the physical properties of niosomes entrapped with the extracts prepared by scCO2 and chloroform film method. The scCO2 extract showed higher unsaturated fatty acid and phenolic contents than the maceration extract. All extracts showed no significant difference of biological activities. The characteristics of niosomes entrapped and not entrapped with the extract prepared by scCO2 and chloroform film method were not different with a unilamellar nano-sized structure and the phase transition temperatures at 80 °C. The gradual decrease trend of the vesicular membrane microviscosity with less membrane rigidity at higher extract concentrations was observed. The scCO2 technique is advantageous for the preparation of the rice bran extracts and niosomes because of no requirement of organic solvents and having less step. © 2010 Elsevier B.V.